A co-delivery nanosystem of chemotherapeutics and DNAzyme overcomes cancer drug resistance and metastasis. Issue 3 (13th December 2017) - Sun, Shu-Pin; Liu, Ching-Ping; Huang, I-Ping; Chu, Chia-Hui; Chung, Ming-Fang; Cheng, Shih-Hsun; Lin, Shu-Yi; Lo, Leu-Wei
Abstract: Multidrug resistance (MDR) constitutes a major problem in the management of cancer and cancer metastasized from primary-source tumor causes cancer-related deaths. Our new approach is the co-delivery of chemotherapy drugs with a transcription-factor-targeting genetic agent to simultaneously inhibit the growth and metastasis of cancer cells. C-Jun is a transcription factor that regulates multidrug resistance-associated protein 1 (MRP1) pump efflux transcription and tumor metastasis. In this work, we reported that mesoporous silica nanoparticles (MSNs) can be functionalized to co-deliver doxorubicin (Dox) and DNAzyme (Dz) to increase cancer cell killing in an additive fashion. The MSNs were sequentially conjugated with Dox into the MSNs' nanochannels and Dz onto the MSNs' outermost surface to target c-Jun as the Dox@MSN-Dz co-delivery system. The Dox-resistant PC-3 cells treated with Dox@MSN-Dz efficiently enhanced the intracellular Dox concentration due to the abrogation of Dox-induced MRP1 expression through the downregulation of c-Jun expression by Dz. Additionally, significant reductions in invasion and migration related to metastasis were also observed in cells treated with Dox@MSN-Dz. Therefore, our results contribute new insight to the treatment of MDR combined metastatic cancer cells, worthwhile for studying its potential for development in clinical translation.